Nanoporous air filtering systems made from renewable sources: benefits and challenges - Dutta, Arnab; Karamikamkar, Solmaz; Nofar, Mohammadreza; Behzadfar, Ehsan (Royal Society of Chemistry (RSC), 2024)
Nanoporous air filtering systems made from renewable sources offer more sustainable alternatives for filter structures from conventional polymers.